English Self-concept: The portrait of English Speaking performance of Indonesian Nursing Students - Apriliyanti, Retno; Nurhayati, Susi (Indonesian Journal Publisher, 2025)
Recognizing the target level of teaching competency is crucial; matching the level of proficiency of students with teaching style will make the learning goal evident. As noted in mandatory competency in learning goals, nursing curriculum demands communication competency, and English has become a worldwide requirement for cross-national language, which will play a role as a supplementary skill for nursing students to graduate. The purpose of this study was to examine how Indonesian nursing students portrayed their English self-concept in relation to their English speaking competence. The sample size is 93 nursing students, and the study methodology is a relationship with convenience or accidental sampling procedures. Marsh, Parker, and Smith (1992) created the Self-description assessment II scale that was used to gather data. According to bivariate study, English self-concept is unrelated to English speaking performance. The r-correlation was larger than 0.05, suggesting that no meaningful relationship exists between the two variables. The average English self-concept score is 82.50, but the average speaking English performance score is 2.44. More cues are needed for EFL students to improve their speaking by managing their English self-concept as a means to create a speaking English environment; this situation should be generated at all educational levels